2022
DOI: 10.1017/s0022215122002602
|View full text |Cite
|
Sign up to set email alerts
|

Changes in sleep performance and chronotype behaviour after vestibular rehabilitation in unilateral vestibular hypofunction

Abstract: Objective This study aimed to investigate changes in sleep parameters and self-perceived sleep quality in unilateral vestibular hypofunction participants after vestibular rehabilitation. Method Forty-six unilateral vestibular hypofunction participants (before and after vestibular rehabilitation) along with a control group of 60 healthy patients underwent otoneurological examination, a one-week actigraphy sleep analysis and a series of self-report and performance measures. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Moreover, these combined findings lead to the hypothesis that chronic or long-term vestibular disorders such as unilateral vestibular hypofunction have an even greater negative impact on sleep quality than acute vestibular problems [ 19 ]. Conversely, interventions of vestibular rehabilitation improved sleep parameters in patients with unilateral vestibular hypofunction [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, these combined findings lead to the hypothesis that chronic or long-term vestibular disorders such as unilateral vestibular hypofunction have an even greater negative impact on sleep quality than acute vestibular problems [ 19 ]. Conversely, interventions of vestibular rehabilitation improved sleep parameters in patients with unilateral vestibular hypofunction [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In humans, epidemiologic evidence supports that adults with vertigo have a higher risk for abnormal sleep duration ( 85 ); conversely, in patients with sleep complains, sleep architecture variation has been associated with vestibular symptoms ( 86 ). Additionally, clinical studies have shown that persistent sleep disturbance after vestibular rehabilitation is related to handicap severity ( 87 ), while rehabilitation for unilateral vestibular disease is associated to improvement of the quality of sleep ( 88 ). However, these variables interact with stress, with a bidirectional relation between stress and sleep quantity, in which worse sleep quantity and continuity may predict higher next-day stress ( 89 ).…”
Section: Discussionmentioning
confidence: 99%